2019
DOI: 10.1093/mnrasl/slz070
|View full text |Cite
|
Sign up to set email alerts
|

The Fall of a Giant. Chemical evolution of Enceladus, alias the Gaia Sausage

Abstract: We present the first chemical evolution model for Enceladus, alias the Gaia Sausage, to investigate the star formation history of one of the most massive satellites accreted by the Milky Way during a major merger event. Our best chemical evolution model for Enceladus nicely fits the observed stellar [α/Fe]-[Fe/H] chemical abundance trends, and reproduces the observed stellar metallicity distribution function, by assuming low star formation efficiency, fast infall time scale, and mild outflow intensity. We pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
117
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 61 publications
(76 reference statements)
14
117
1
Order By: Relevance
“…This Plume is largely responsible for the marked change in radial anisotropy with increasing [Fe/H] in the RRL sample, which resembles the one Belokurov et al (2018) found in a sample of main-sequence stars. In all respects, the kinematics of the Plume RRL closely resemble as the 'Gaia-Sausage' or 'Gaia-Enceladus' , which appear to have their origin in a large dwarf galaxy that merged with the MW (see also Myeong et al 2018;Kruijssen et al 2019;Mackereth et al 2019a;Vincenzo et al 2019;Fattahi et al 2019). The MDF of the Plume RRL is skewed towards higher metallicity than the MDF of other high-energy RRL, many of which are members of either the prograde Helmi-Stream or retrograde groups that may be part of the 'Sequoia' galaxy (Myeong et al 2019).…”
Section: Discussionmentioning
confidence: 91%
“…This Plume is largely responsible for the marked change in radial anisotropy with increasing [Fe/H] in the RRL sample, which resembles the one Belokurov et al (2018) found in a sample of main-sequence stars. In all respects, the kinematics of the Plume RRL closely resemble as the 'Gaia-Sausage' or 'Gaia-Enceladus' , which appear to have their origin in a large dwarf galaxy that merged with the MW (see also Myeong et al 2018;Kruijssen et al 2019;Mackereth et al 2019a;Vincenzo et al 2019;Fattahi et al 2019). The MDF of the Plume RRL is skewed towards higher metallicity than the MDF of other high-energy RRL, many of which are members of either the prograde Helmi-Stream or retrograde groups that may be part of the 'Sequoia' galaxy (Myeong et al 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Tolstoy et al 2009). Recent Galactic chemical evolution modelling suggest that this knee could be at around [Fe/H] ≈ −2.5 (Vincenzo et al 2019). The corresponding plateau value of [O/Fe] ≈ 0.7 at the lowest metallicities [Fe/H] −2.5 in the unclassified stars, is roughly 0.1 dex higher than that of the high-α halo population.…”
Section: The Low-metallicity Starsmentioning
confidence: 95%
“…Even though this is in fact the main tenet of the popular sub-field of Astrophysics known as Galactic Archaeology, not many such forensic studies are currently on record. Large numbers of detailed chemical abundances have so far only been collected and analysed for two stellar halo structures: the Sagittarius stream (see Monaco et al 2007;Chou et al 2007;de Boer et al 2015;Carlin et al 2018;Hayes et al 2020) and the Gaia Sausage (see Nissen & Schuster 2010;Helmi et al 2018;Mackereth et al 2019;Vincenzo et al 2019;Molaro et al 2020;Feuillet et al 2020). Additionally, a small number of stars in globular cluster streams have been under the magnifying glass of high-resolution spectroscopy (e.g.…”
Section: Introductionmentioning
confidence: 99%